Anti-osteoporotic effects of melatonin and misoprostol in glucocorticoid-induced osteoporosis: An experimental study - Kutlu, Orkide; Üzüm, İsa and Durmuşcan, Mustafa and Kekilli, Ersoy and Parlakpınar, Hakan and Kutlu, Nurettin Onur (Journal of Surgery and Medicine, 2019)
Aim: Although there are some treatment options for glucocorticoid induced osteoporosis (GIO), new drug alternatives are still needed. In this study, we aimed to determine the protective effects of misoprostol and melatonin in an experimental GIO model. Methods: The rats were grouped into four, with 10 rats in each group. The 1st group was chosen as the control group, which were not intervened with. Group 2 was the steroid group, group 3 the misoprostol group and group 4, the melatonin group. To the rats in groups 2, 3 and 4, 10 mg/kg subcutaneous methylprednisolone was administered for 28 days. To the rats of the 3rd group, 200 mg/day misoprostol was given per day by a cannula to the stomach. The rats in the 4th group received 5mg/kg intraperitoneal melatonin during this 28-days period. Lumbar vertebrae and femur bone mineral density (BMD) of all rats were measured by Dual-energy X-ray absorptiometry (DEXA) and assessed in pre- and post-treatment periods. Results: In the steroid group, when the pre- and post-treatment-BMD values of the rats were compared, statistically significant decreases were found in vertebrae, whole femur, femur proximal, femur diaphysis and distal femur bone regions (P=0.011, P=0.005, P=0.007, P=0.005 and P=0.013; respectively). In the misoprostol group, a statistically significant decrease was observed only in the whole femur region (P=0.012) when the pre- and post-treatment BMD values of the rats were compared, while no significant changes were observed in vertebrae, femur proximal, femur diaphysis and distal femur bone regions (P=0.093, P=0.401, P=0.161 and P=0.123; respectively). In the melatonin group, when the pre- and post-treatment BMD values of the rats were compared, a statistically significant decrease was observed only in the vertebrae region (P=0.009), no significant changes were observed in whole femur, femur proximal, femur diaphysis and distal femur bone regions (P=0.386, P=0.445, P=1.000 and P=0.483; respectively). Conclusion: Positive effects of misoprostol and melatonin on bone metabolism were determined in this experimental study. Misoprostol and melatonin seem to be potential agents that can be used in the prevention of GIO.